Entre o Império do Mali e o «Islão marítimo». O impacto dos legados e das literacias islâmicas na África portuguesa - Łukaszyk, Ewa A. (Studia Romanica Posnaniensia, 2023)
The article presents the impact of the Islamicate populations and literacies in Portuguese colonial literature and scholarship. The main ethnic group that focused the attention of the colonisers were the aggressive, dominant Fulani portrayed in the novels of Fausto Duarte, Auá and A Revolta. Their usages and traditions were studied by the first Portuguese ethnographers and ethnohistorians with almost satisfactory results. On the other hand, Islam in the oriental part of the Portuguese colonial empire (Mozambique) was much less understood. The Portuguese paid greater attention to the aggressive, jihadist movements in West Africa than to the relatively less conspicuous Sufi movements that developed in the port cities and islands along the East African coast. Overall, the process of Islamicization of the territories controlled by the Portuguese went on unhindered or even accelerated during the colonial period.